Historical perspectives in prosthetics and orthotics area for rehabilitation of persons with locomotors disabilities from independence to current scenario - Gouri RajendraKumar Chechani; Rajendra Kumar Chechani (Journal of Integrated Health Sciences)
History of prostheses in India is very ancient from Rigveda, the Asvini brothers (vedic gods of healing and medicine) replaced Vispala's (horse of Prince Khela) broken leg with an artificial one. As years passes, many more evidence of uses of artificial limb came into existence. The purpose of this review is to show the evolutional era of prosthetics and orthotics in India as we are celebrating India's Azadi ka Amrit Mahotsav, 75 years of Independence. How work has been done to serve the Divyangjan's in their community level under the Indian government's flagship schemes, with the help of different national institutions, regional centers, nongovernment organizations, and many more. Along with the development of institutions and organizations, technology also developed the devices at that much level that one can trust these prosthetic and orthotic devices and live independently. Not only that, people are actively taking part in sports and recreations and participating in the paralympics and making India proud.